P221 Does virtual group breathing pattern retraining improve symptoms of breathlessness in patients with breathing pattern disorder following COVID-19 infection?. (11th November 2022) - Gore, R; Williamson, L; Elliott-Cooper, T; Roze, K; Heightman, M; Hillman, T; Livingston, R
Abstract : British Thoracic Society (BTS) guidelines recommend assessment of breathing pattern disorder (BPD) for ongoing breathlessness post COVID-19 infection. 23.7% of patients attending post covid clinic were referred for breathing pattern retraining (BPR) (Heightman et al, 2021) 2 and evidence suggests that BPR can improve breathlessness arising from BPD (British Thoracic Guidance, 2020) 1 . Due to large referral numbers, limited specialist work force and increased waiting times following redeployment during the Covid pandemic, virtual group BPR treatment (VGT) was trialled as an alternative to one-to-one intervention. Data were collected from patients referred for BPR following completion of post Covid-19 multidisciplinary clinic assessment. Breathlessness (Dyspnoea 12- D12), breathing pattern (Brompton Breathing Pattern Assessment Tool – BPAT) and fatigue (Fatigue Assessment Scale – FAS) were assessed by a specialist Physiotherapist on referral and completion of VGT. VGT consisted of 6, 1 hour, physiotherapist led sessions run fortnightly using a virtual platform. The programme included BPR at rest and on exertion, activity management, pacing advice, psychological health advice and relaxation. The interactive nature of the sessions also enabled facilitated peer support. Group size was 6–10 participants. A Wilcoxon Sign Rank test was used to compare pre and post treatment data. 32 patients enrolled, 26 completed the groups in full across 4 cohorts. 6 dropped out due to work or medical reasons. Complete data sets (n=18) were analysed (16 female, 2 male, median age= 46, mean 15 months post infection). VGT for 26 patients saved 52 hours of clinician time compared with usual, one-to-one intervention Improvement in BPAT, D12 and FAS were statistically significant ( table 1 ) Virtual group BPR treatment improved breathing pattern and breathlessness for patients within the post covid BPD. With social distancing regulations, VGT offers an effective alternative to face to face group treatment. This saved clinician time which could enable reduced wait times for treatment. References: British Thoracic Society. British thoracic society guidance on respiratory follow up of patients with a clinico-radiological diagnosis of COVID-19 pneumonia, 2020. Heightman M, Prashar J, Hillman TE, et al . Post-COVID-19 assessment in a specialist clinical service: a 12-month, single-centre, prospective study in 1325 individuals. BMJ Open Resp Res, 2021;8 .